Reorganizing Christian Education After the Pandemic in Indonesia: A Need for Learning Management - Kristyana Kristyana; Sri Wahyuni; Roy Pieter; Vernando Purba; Meri K.D. Sitepu; Ronny Simatupang; Sandy Ariawan (IJECA (International Journal of Education and Curriculum Application), 2021)
This study aimed to analyze the influence of learning management on the learning achievements of Christian education. The data analysis methods used were simple correlation analysis method, simple linear regression analysis and t test. The samples in this study were 95 Christian students of state senior high school. The relationship between Learning Management (X) and Learning Achievement (Y) amounted to 0.661. The correlation relationship rate was in the high category. So there was a positive relationship with the low category between Learning Management and Student Learning Achievement. R Square of 0.437 this showed that the influence of Learning Management with Student Learning Achievement was 43.70% and the remaining 56.3% was influenced by other factors not discussed in this study. The t test was conducted by comparing tcount and ttable. In accordance with the testing requirements that tcount (3,580) > ttable (0,2796), this means that the variables of Learning Management have a positive and significant influence on the Student Learning Achievement. Thus Ho refused and Ha was accepted. Considering the high influence of learning management on learning achievement, teachers need to reorganize the learning patterns of Christian education. The focus of change is directed at planning, organizing, directing, and controlling the materials and the class as well.